Blood Biomarkers for Evaluation of Perinatal Encephalopathy - Graham, Ernest M.; Burd, Irina; Everett, Allen D.; Northington, Frances J. (Frontiers in Pharmacology, 2016)
Recent research in identification of brain injury after trauma shows many possible blood biomarkers that may help identify the fetus and neonate with encephalopathy. Traumatic brain injury shares many common features with perinatal hypoxic-ischemic encephalopathy. Trauma has a hypoxic component, and one of the 1st physiologic consequences of moderate-severe traumatic brain injury is apnea. Trauma and hypoxia-ischemia initiate an excitotoxic cascade and free radical injury followed by the inflammatory cascade, producing injury in neurons, glial cells and white matter. Increased excitatory amino acids, lipid peroxidation products and alteration in microRNAs and inflammatory markers are common to both traumatic brain injury and perinatal encephalopathy. The blood-brain barrier is disrupted in both leading to egress of substances normally only found in the central nervous system. Brain exosomes may represent ideal biomarker containers, as RNA and protein transported within the vesicles are protected from enzymatic degradation. Evaluation of fetal or neonatal brain derived exosomes that cross the blood-brain barrier and circulate peripherally has been referred to as the “liquid brain biopsy”. A multiplex of serum biomarkers could improve upon the current imprecise methods of identifying fetal and neonatal brain injury such as fetal heart rate abnormalities, meconium, cord gases at delivery, and Apgar scores. Quantitative biomarker measurements of perinatal brain injury and recovery could lead to operative delivery only in the presence of significant fetal risk, triage to appropriate therapy after birth and measure the effectiveness of treatment.